Knowledge and practice of stretching by university students. - Merino-Marban, Rafael; Aguilar-Reguero, José Luis; Smuka, Ingrida; Mayorga-Vega, Daniel (Editura Universitatea din Pitesti, 2023)
Flexibility is a somewhat complicated concept to define due to the large number of terms and components it encompasses and there are many stretching techniques we can use. However, the knowledge that university students of Physical Education have, according to previous studies, is often very scarce. The purpose of this study was to obtain information about flexibility and the practical application of stretching techniques possessed by students at the Latvian Academy of Sports Education in Riga, Latvia. A sample of 159 volunteer students participated in the present study, (male n = 83; female n = 76) from four courses and the first year of Master's degree in Physical Education (age 21.51 ± 2.40 years). The students completed the survey consisting of 14 questions related to their knowledge of stretching techniques and part of the training session in which they perform stretching. The knowledge and use of stretching techniques was low for both university and Master´s students, but the third-year students had more knowledge (1.87 ± 0.672 vs. 0.84 ± 0.569). Most of the participants do not usually have dedicated stretching sessions and if they do, they are rare (0.20 ± 0.659). Most participants tend to stretch during both warm-up and cool-down. The knowledge of university students about flexibility and stretching is insufficient. In conclusion, we agree that the use of stretching by university students during their training sessions is low. It would be advisable to implement intervention programmes and sessions dedicated solely to the development of this physical quality at the school and/or university.
Política de acceso abierto de la revista: https://journal.unnes.ac.id/sju/jpes/open
Keywords: Educación física; Development of flexibility; static-passive technique; bouncing technique; practical application flexibility